China : has the last opportunity passed by?! - Wu, Guang, 1962- (China in the 21st century (Commack, N.Y.), 2009)
"The first couple of years at the beginning of 21st century were a historically unique opportunity for the Chinese, not only because the Chinese economy grew at an amazingly rate, which shocked the world, but also more importantly the US was busy in the war against terror, and Russia was still not recovered from the collapse of the Soviet Union and was undergoing another painfully chaotic phase in her modern history. Japan was in deep trouble with her economy, and the reunion of two Germanys overwhelmed Germany. The Chinese economy will continue growing, although at a lesser rate, but the window of opportunity, through which China can become a world power, has shrunk. This was a unique opportunity for the Chinese people over her 5000-plus-year history. In this book the author explores what makes a country great, why the Chinese might have lost this opportunity, what the Chinese lack, what the Chinese thinking pattern is, what Chinese generation kinetics and dynamics are, what Chinese war is all about, and what the future may hold."--Publisher's description.